2020
DOI: 10.3889/oamjms.2020.3323
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Antibiotics Self-medication Practices among University Students in Cairo, Egypt

Abstract: BACKGROUND: Self-medication is a practice with major global implications, especially with antibiotics intake. Self-medication among future health-care professionals could affect their way in prescribing medication in the future. AIM: This study was conducted to estimate the magnitude and the determinants of antibiotics self-medication practices and to describe the pattern of antibiotics abuse among undergraduate university students. METHODS: A cross-section study was conducted among 563 medical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…Several causes can be responsible for the increased incidence of drug-resistance detected in the present study. The prime reason may be the common practice in Egypt where almost all patients-before hospital admission-take diverse antibiotics either prescribed by doctors or self-medication due to over-the-counter antibiotics administered mostly in an improper dose and for an inadequate period [37,38]. Other potential causes are the geographical divergence as well as the genetic variations among pathogens from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several causes can be responsible for the increased incidence of drug-resistance detected in the present study. The prime reason may be the common practice in Egypt where almost all patients-before hospital admission-take diverse antibiotics either prescribed by doctors or self-medication due to over-the-counter antibiotics administered mostly in an improper dose and for an inadequate period [37,38]. Other potential causes are the geographical divergence as well as the genetic variations among pathogens from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were still some misconceptions and malpractices reported among medical students/professionals. [36][37][38] Regarding self-medication with antibiotics, 62.2%, 36 65.9% 39 and 77.7% 37 of medical students reported such practice. These rates are higher than that observed among nonmedical students in the current study (39.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these factors are in line with those reported by Ocan and colleagues in a review on developing countries (65). Accessibility, affordability, and conditions of health facilities, as well as the health-seeking behaviors were among the factors identified by Torres and associates in LMIC (17). Low educational status is the most frequently reported factor associated with SMA, warranting the need to promote literacy among communities in Africa as a vital strategy to also reduce SMA.…”
Section: Discussionmentioning
confidence: 87%
“…Five studies reported male gender (32,40,43,45,53), while 2 studies presented the female gender (20,51). Other associated factors reported were low income or unemployment (52,55), young age <30 years (17,42,55), middle-age 30 to 60 years (20,51), the remoteness of health facility (48,53), and perceived long waiting time at health facilities (43,53) [Table 4].…”
Section: Resultsmentioning
confidence: 99%